Effects of carbon tetrachloride on rat liver plasmalemmal calcium adenosine triphosphatase. - Izutsu, K. T. (1978)
Calcium adenosine triphosphatase (Ca-ATPase) activity in rat liver plasma membrane fractions prepared by zonal centrifugation was studied for sensitivity to carbon tetrachloride (CCl4). Levels of Ca-ATPase activity in such membrane fractions from animals given CCl4 by gastric intubation were no different from those in plasmalemmal fractions obtained from control rats. When the fractions were incubated in vitro, however, this enzyme activity was inhibited by the presence of CCl4 in a dose-dependent manner. Moreover, inhibition of Ca-ATPase could be reversed by the removal of CCl4. These results would explain the observed increase in hepatic calcium content following the administration of CCl4 if the Ca-ATPase were capable of actively extruding calcium and if this extrusion mechanism proved sensitive to CCl4 present on or about the hepatocytes.